Terrestrial biodiversity of the Isthmus of Tehuantepec and international environmental conservation policies. Case of Payment for Environmental Service mode - FLORES MONDRAGÓN, Gonzalo (Utopía y Praxis Latinoamericana, 2023)
The strategies of environmental conservation and use of natural resources at the national level, designed by international financial institutions (WB, IMF, IDB) and applied by the federal governments of Mexico during the last 30 years, have had the objective of control, expropriation, privatization and exploitation of these resources in favor of large transnational capitals. In the region of the Isthmus of Tehuantepec this problem is more than evident. The strategy of conservation and sustainable use of biodiversity have not stopped the devastation of this resource and have not favored the indigenous and peasant communities of the region (custodians of this wealth), but, on the contrary, have allowed their exploitation and privatization in favor of large companies.